Factors associated with shorter length of admission among people with dementia in England and Wales: retrospective cohort study - Kate Seers; William Lee; Alistair Burns; Mike Crawford; Sophie Staniszewska; Alan Quirk; Rahil Sanatinia; Peter Crome; Fabiana Gordon; Chloe Hood; Gemma Zafarani (BMJ Open, 2021)
Objectives To identify aspects of the organisation and delivery of acute inpatient services for people with dementia that are associated with shorter length of hospital stay.Design and setting Retrospective cohort study of patients admitted to 200 general hospitals in England and Wales.Participants 10 106 people with dementia who took part in the third round of National Audit of Dementia.Main outcome measure Length of admission to hospital.Results The median length of stay was 12 days (IQR=6–23 days). People with dementia spent less time in hospital when discharge planning was initiated within 24 hours of admission (estimated effect −0.24, 95% CI: −0.29 to −0.18, p<0.001). People from ethnic minorities had shorter length of stay (difference −0.066, 95% CI: −0.13 to −0.002, p=0.043). Patients with documented evidence of discussions having taken place between their carers and medical staff spent longer in hospital (difference 0.26, 95% CI: 0.21 to 0.32, p<0.001). These associations held true in a subsample of 669 patients admitted with hip fracture and data from 74 hospitals with above average carer-rated quality of care.Conclusions The way that services for inpatients with dementia are delivered can influence how long they spend in hospital. Initiating discharge planning within the first 24 hours of admission may help reduce the amount of time that people with dementia spend in hospital.